1968
DOI: 10.1017/s0031182000073406
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the absorption of amino acids by larval tapeworms (Cyclophyllidea: Taenia crassiceps)

Abstract: Larvae of Taenia crassiceps have been shown to absorb L-valine and L-methionine by a process of active transport. Uptake is maximal at about 43 °C and a pH of about neutrality, and concentration against a gradient has been demonstrated. In advanced larvae, the absorption mechanism has been shown to be specific for neutral aliphatic amino acids, with an uncharged amino group in the α-position. Competitive inhibitions of uptake have been demonstrated in the presence of other amino acids.Comparison has been made … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
1

Year Published

1970
1970
1990
1990

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 4 publications
2
9
1
Order By: Relevance
“…Some controversy exists concerning proline uptake by metacestodes of Taenia crassiceps. Haynes & Taylor (1968) and Haynes (1970) considered proline absorption to be mediated, but this view has been disputed by Pappas & Read (1973), who concluded that proline uptake was entirely by diffusion. Separate transport loci for imino acids have been described in a number of vertebrate systems (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Some controversy exists concerning proline uptake by metacestodes of Taenia crassiceps. Haynes & Taylor (1968) and Haynes (1970) considered proline absorption to be mediated, but this view has been disputed by Pappas & Read (1973), who concluded that proline uptake was entirely by diffusion. Separate transport loci for imino acids have been described in a number of vertebrate systems (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in vitro biosynthetic labelling of proteins with radioactive methionine resulted in low incorporation of radioactive label into proteins by T. crassiceps. Haynes & Taylor (1968) showed that during incubation of T. crassiceps metacestodes in the presence of methionine for 1-4 h, less than 1 % of total methionine uptake was incorporated into protein as compared with 12% for glutamic acid. Although methionine is the standard label used for in vitro biosynthetic labelling, glutamic acid may prove to be a more appropriate source of radioactive label for this parasite.…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 H]Proline uptake was not inhibited by unlabelled proline, and [ 14 C]glutamic acid uptake was not inhibited by unlabelled glutamic acid nor by malic acid (Table 2). Malic acid was reported by Haynes & Taylor (1968) to be a very effective inhibitor of glutamic acid uptake by T. crassiceps metacestodes. These data (Table 2) (Figs.…”
Section: Absorption Of Amino Acidsmentioning
confidence: 99%
“…The insignificant radioactivity associated with both types of larvae from all incubation periods was attributed to non-specific adsorption of inulin to the external surface of larvae. Haynes & Taylor (1968) and Haynes (1970) reported that glutamic acid and proline are transported by advanced larvae of T. crassiceps by systems which were described as specific, with the implication that uptake of these amino acids is specifically mediated rather than occurring by diffusion. Haynes & Taylor (1968) reported that the uptake of glutamic acid was inhibited by aliphatic dicarboxylic acids, i.e.…”
Section: Absorption Of Inulinmentioning
confidence: 99%
See 1 more Smart Citation